Adsorption of Cd (II), Cu (II), and Zn (II) from Aqueous Solution onto Nitrogen-Functionalized Desmostachya bipinnata. (30th March 2013) - Kour, Jagjit; Homagai, Puspa Lal; Cagnin, Massimo; Masi, Antonio; Pokhrel, Megh Raj; Ghimire, Kedar Nath
Abstract : A very simple means of nitrogen functional group grafting onto the backbone of Desmostachya bipinnata is investigated, which is a sacrificial herb in the south Asian region particular to Hindu religion. This natural biomaterial is found to be very effective for metal binding, after treatment with hydrazine monohydrate. The present study explores a comparison of amination processes by considering several options. The maximum metal loading capacities for Cd, Cu, and Zn were found to be 76.80 mg/g, 72.10 mg/g, and 58.16 mg/g, respectively. The kinetic evaluation indicated that the adsorption of Cd, Cu, and Zn onto the biomaterials followed the pseudo second-order rate equation.